Chinese Investment in Advanced Economies: Opportunities and Challenges. (3rd April 2017) - Deng, Ping; Yang, Xiaohua; Wang, Liang; Doyle, Barry
Abstract : With an increasing importance of outward foreign direct investment (OFDI) by multinationals (MNCs) from China in advanced economies, there is a need for deepening our knowledge of these Chinese MNCs not simply regarding their benefits and concerns, but more importantly regarding their dynamic and complex contexts. In this article, we investigate challenges that Chinese investors face in managing multiple embeddedness across heterogeneous contexts and why this multiple contextual embeddedness is particularly evident when Chinese firms acquire Western firms for competitive catch‐up. We contend that the interaction of Chinese investors with various local contexts depends on the extent to which these contexts are not only interrelated, but also overlain by temporal and spatial dimensions of context. Accordingly, contextualizing globalization of Chinese companies temporally and spatially will allow us to better understand their international expansion. More generally, we stress the need to place Chinese OFDI research in its broader context, temporally and spatially, and go beyond the mere institutional or cultural distance variables. Finally, we outline the key contributions from the six articles in this special issue and discuss the future research agenda stimulated by the issues raised in these articles. © 2017 Wiley Periodicals, Inc .